Redescription of Astyanax erythropterus (Holmberg, 1891) (Teleostei: Characiformes: Characidae) from La Plata basin in Argentina - Soneira, Paula (2010)
Astyanax erythropterus (Holmberg, 1891) originally described on the basis of one juvenile, is redescribed herein based on juveniles and adults from the type-localiy. The species differs from its congeners by the combination of 11-13 transverse rows scales above lateral line and 8-10 rows below lateral line; 49-54 perforated scales in the lateral series; iii-v,38-42 anal-fin rays, and dorsal, anal and caudal fins vermilion red in juveniles. The vermilion red coloration of unpaired fins in juveniles of Astyanax is only known in A. correntinus. © 2010 Sociedade Brasileira de Ictiologia.